Hubungan antara Ibu Hamil dengan Kurang Energi Kronis (KEK) dan Kejadian BBLR di RSUD Sultan Muhammad Jamaludin I - Utin Rindy Ferawati; Selasih Putri Isnawati Hadi; Novita Puspita Dewi (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Pregnant women with poor nutritional status or Chronic Energy Deficiency (CED) are at risk of health complications for both the mother and fetus, such as low birth weight (LBW). This study aimed to determine the relationship between pregnant women with CED and the incidence of LBW at RSUD Sultan Muhammad Jamaludin I. The study used a descriptive correlational design with a retrospective approach using secondary data from medical records. The population consisted of 330 respondents, selected by total sampling technique. Univariate and bivariate analyses (Chi-square test) were performed. Most respondents were under 35 years old (66.4%), primigravida (62.0%), in their third trimester (100%), and had tertiary education (54.2%). Most did not have LBW infants (91.8%), and most were not diagnosed with CED (24.1%). Chi-square analysis showed a significant correlation (p=0.001) with an Odds Ratio of 11.566, indicating that CED significantly influences the likelihood of LBW.